CLINICAL COURSE AND FEATURES OF DISORDER OF HEMOSTASIS IN PATIENTS WITH IMMUNE MICROTHROMBOVASCULITIS - Islamova, Z.S.; Babadjanova, Sh.A.; Kurbonova, Z.Ch. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: To study the clinical course, hemostatic parameters in patients with immune microtrombovasculitis. Materials and methods: Usual frequency of clinical forms, parametres of hemostasis was studied in 135 patients with immune microtrombovasculitis. Results: The most common clinical form of immune microthrombovasculitis is the cutaneous-articular form (62.2%), women get sick in 67.3% of cases, men 32.7%. The study of hemostasis indicates increase of platelet aggregation, increase of concentration of number of plasma coagulation factors and the appearance of fibrin degradation productes. Conclusion: The study of hemostasiological parameters in immune microtrombovasculitis indicates hypercoagulation.